2019
DOI: 10.1039/c9cc05853b
|View full text |Cite
|
Sign up to set email alerts
|

Copper-catalyzed radical approach to allenyl iodides

Abstract: A copper-catalyzed 1,4-addition reaction of arylsulfonyl iodides with 1,3-enynes afforded various allenyl halides in high yields under mild conditions via a radical mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 71 publications
1
26
0
Order By: Relevance
“…In 2021, the Liu group reported a copper-catalyzed radical asymmetric 1,4-carboalkynylation of 1,3-enynes with terminal alkynes (Figure b), which offers an efficient method for the synthesis of alkyne-containing tetrasubstituted chiral allenes. In addition, there are also several 1,4-difunctionalization reactions of 1,3-enynes realized by the groups of Bao, Wang, Li, and others . Despite these promising advances, a new method for producing multisubstituted allene derivatives with greater functional group tolerance and improved molecular diversity is still highly desired.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…In 2021, the Liu group reported a copper-catalyzed radical asymmetric 1,4-carboalkynylation of 1,3-enynes with terminal alkynes (Figure b), which offers an efficient method for the synthesis of alkyne-containing tetrasubstituted chiral allenes. In addition, there are also several 1,4-difunctionalization reactions of 1,3-enynes realized by the groups of Bao, Wang, Li, and others . Despite these promising advances, a new method for producing multisubstituted allene derivatives with greater functional group tolerance and improved molecular diversity is still highly desired.…”
Section: Introductionsupporting
confidence: 59%
“…On the basis of above experimental results and previous reports, ,, a plausible mechanism is proposed (Scheme ). Initially, the LCu­(I) species A reacts with TBHP to afford the LCu­(II)­OH species B and a t- BuO radical C via a single electron transfer process.…”
Section: Results and Discussionmentioning
confidence: 99%
“…[31] Ma et al have reported copper(I) catalyzed radical methodology to prepare allenyl iodides from 1,3-enynes. [32] In the presence of catalytic amount of Cu I I, 1,3-enynes 60 react with sulfonyl iodides 61 to form allenyl iodides 62 in high chemical efficiency (Table 2). The reaction showed very good scope with respect to the 1,3-enynes as well as the sulfonyl iodides.…”
Section: Radical Additions To Enynesmentioning
confidence: 99%
“…And then, radical addition of the sulfonyl radical with 1,3enynes affords two resonant radical intermediates: alkyl radical Int-62 and allenyl radical Int-63. 74 Subsequently, the radical cross coupling of allenyl radical Int-63 with the NO radical generates the allenyl intermediate Int- 64, which undergoes successive isomerization and intramolecular nucleophilic cyclization to produce the desired products 119 in the presence of InBr 3 . The authors also demonstrated that InBr 3 plays an important role in this cascade pathway.…”
Section: Indium Catalystsmentioning
confidence: 99%